Co-creation: a B2C and B2B comparative analysis. Issue 6 (2nd September 2019) - D'Andrea, Fernando Antonio Monteiro Christoph; Rigon, Filipe; Almeida, Ana Carolina Lopes de; Filomena, Bertran da Silveira; Slongo, Luiz Antonio
Abstract : Purpose: The purpose of this paper is to qualitatively analyze and compare people's objectives when participating in two sets of co-creation initiatives – business-to-consumer (B2C) and business-to-business (B2B) – to what the theory in the field states about that participation. Design/methodology/approach: A qualitative approach has been adopted; it uses laddering, a qualitative technique, in a novel manner through the analysis of an abstract product: the co-creation process. Findings: Results in B2C point to a disconnection between the motivation of participants and what the theory suggests that should be expected from a co-creation agenda. In the B2B setting, the disconnections are much smaller. Research limitations/implications: The research used small and narrow samples. Additionally, the research considers only the consumers' perspective. Practical implications: Considering the context in which they compete (industrial or consumer market), companies must come up with better selection criteria for co-creators and must be more specific in setting and pursuing the goals of the co-creation projects. By doing so, organizations can achieve more fruitful results in those innovation initiatives. Originality/value: The present study is innovative in the use of laddering to understand not a product nor a service, but a process: co-creation. The study reveals that, despite the buzz about co-creation, practical examples suggest that this process may not be as fruitful or satisfying as the theories suggest.